PILOT STUDY OF FACTORS AFFECTING PATIENT-COMPLIANCE TO CURATIVE TREATMENT OF CANCER - Chitra Venkateswaran
A survey was conducted among patients/patient carers with definite diagnosis of cancer to identify if there was compliance to suggested curative therapy and if they did not choose to or if there was a delay or interruption in treatment, what were the factors affecting this non compliance. 37 patients in Calicut district were included. A Malayalam questionnaire was developed to obtain information from patients or primary carers of patients. Volunteers were trained to use the questionnaire and record the information. 33.33